Changed sensitivity to antigen in a gut epithelium treated with bile salts. - Baird, A. W. (Nature Publishing Group, 1985)
Colonic epithelia from guinea-pigs, sensitized by feeding with cow milk, responded to antigen (beta-lactoglobulin) challenge when applied to the serosal, but not the mucosal, side of the tissue. The response, under short circuit conditions, was an inwardly directed current due to chloride secretion. Two detergents, deoxycholate and Triton X-100, caused the basal short circuit current to decrease and transepithelial conductance to increase when applied to the mucosal surface. After removing detergents from the bathing solution tissues now responded to antigen challenge from the mucosal side, without impairment of the overall response. There was a correlation between the conductance change induced by detergents and the fraction of the total response which could be elicited form the mucosal side of the tissue. It was concluded that models of local hypersensitivity reactions to ingested foodstuffs require both development of immunological sensitivity plus increased permeability to antigen. The role of bile salts in inducing the latter is discussed.